Emprising revival of Telangana power sector: Analysis from an Indian state. Issue 1 (30th June 2020) - Mohammed, Shameem P.; Chittedi, Krishna Reddy
Abstract : The paper discusses the new 24‐hr power supply to agricultural sector scheme of Telangana state in India. The first of its kind scheme that is fully funded by the state government set a new example for agrarian states in India. The paper explains the energy demand and supply management, fiscal and infrastructural preparedness of the scheme along with environmental concerns. The primary survey report from two villages testifies people's aspirations about the new scheme. Rational power consumption by farmers is identified as key factor of this scheme that will enable government to overcome challenges on sustainability of the scheme.